Revisiting the Public Sphere: Communication, Digital Mobilization, and Misinformation in Indonesia’s 2019 and 2025 Mass Demonstrations - Nieke Monika Kulsum; Selamat Ginting; Agus Salim (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
This study investigates the evolving role of communication in shaping Indonesia’s mass demonstrations in 2019 and 2025, two pivotal episodes reflecting civic discontent and the transformation of the digital media landscape. Grounded in agenda-setting theory, framing theory, and Habermas’s public sphere theory, this research examines how digital communication has shifted from rational discourse to affective and algorithmic mediation. The study hypothesizes that changes in media ecology influence not only public mobilisation but also the legitimacy of civic movements. Employing a comparative digital ethnography, this research analyses online communication practices, visual narratives, and misinformation across platforms such as Twitter (2019) and TikTok/Instagram (2025). Data were collected from user-generated content, hashtags, and visual artefacts, followed by interpretive coding to explore evolving communication logics and the algorithmic amplification of affective messages. Findings reveal a transformation from the networked public sphere of 2019—dominated by text-based civic idealism—to the algorithmic public sphere of 2025, characterised by visual storytelling, emotional contagion, and platform-driven visibility. While digital networks expanded participatory opportunities, they simultaneously fostered misinformation, algorithmic manipulation, and emotional polarisation. These dynamics illustrate how classical communication theories require integration with affective and algorithmic dimensions to explain contemporary activism. The results align with previous studies on digital democracy, highlighting both empowerment and control in mediated civic engagement. The study concludes that Indonesia’s evolving digital public sphere embodies both the promise and the peril of democratic communication. It underscores the dual function of communication—as a vehicle for civic empowerment and as a mechanism of algorithmic governance—in shaping public trust and deliberation.